Theoretical study of the reaction mechanism of a series of 4-hydroxycoumarins against the DPPH radical - Rodríguez, Sergio Antonio (2014)
Structural, electronic and energetic characteristics of a series of 4-hydroxycoumarin derivatives have been studied using DFT to elucidate the mechanisms involved in their antiradical activities against DPPH radical. Different mechanisms were examined. The thermodynamic parameters obtained were BDE, IP, ETE, PA and PDE, both in gas and methanolic phase. The evaluation of these parameters allowed to conclude that the most probable mechanism was HAT. In addition, the transition state (TS) and pre-TS complex for the reaction of hydroxycoumarins and DPPHradical dot were calculated. The results provide a physicochemical understanding of the hydrogen abstraction of a no-phenolic hydroxyl.